The Effects of Profitability and Environmental Performance on Firm Value: The Mediating Role of Green Accounting Disclosure in Energy Sector Companies Listed on the Indonesia Stock Exchange - Salis Ragil Wilujeng; Dyarini Dyarini (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study is motivated by inconsistent findings regarding the effects of profitability, environmental performance, and green accounting disclosure on firm value, particularly in the energy sector, which faces substantial environmental risks. The study examines the direct effects of profitability and environmental performance on firm value and the mediating role of green accounting disclosure. Using a quantitative causal research design, this study analyzes 34 energy sector companies listed on the Indonesia Stock Exchange during 2020–2024, selected through purposive sampling. Secondary data were collected from annual reports, sustainability reports, and PROPER reports. Profitability was measured by Return on Equity (ROE), environmental performance by PROPER ratings, firm value by Tobin’s Q, and green accounting disclosure by the GRI 300 Index. Data were analyzed using panel data regression and Sobel mediation tests. The results indicate that profitability has no significant effect on firm value or green accounting disclosure. In contrast, environmental performance positively affects both firm value and green accounting disclosure. Green accounting disclosure negatively affects firm value and mediates the relationship between environmental performance and firm value, but not the relationship between profitability and firm value. These findings highlight the importance of environmental performance and sustainability disclosure in shaping firm value within the energy sector.